Epigenetic Mechanisms of Aluminum-Induced Neurotoxicity and Alzheimer’s Disease: A Focus on Non-Coding RNAs - Aschner, Michael; Skalny, Anatoly V.; Santamaria, Abel; Rocha, Joao B. T.; Mansouri, Borhan; Tizabi, Yousef; Madeddu, Roberto; Lu, Rongzu; Lee, Eunsook; Tinkov, Alexey A. (Neurochemical research, 2024)
Aluminum (Al) is known to induce neurotoxic effects, potentially contributing to Alzheimer’s disease (AD) pathogenesis. Recent studies suggest that epigenetic modification may contribute to Al neurotoxicity, although the mechanisms are still debatable. Therefore, the objective of the present study was to summarize existing data on the involvement of epigenetic mechanisms in Al-induced neurotoxicity, especially AD-type pathology. Existing data demonstrate that Al exposure induces disruption in DNA methylation, histone modifications, and non-coding RNA expression in brains. Alterations in DNA methylation following Al exposure were shown to be mediated by changes in expression and activity of DNA methyltransferases (DNMTs) and ten-eleven translocation proteins (TETs). Al exposure was shown to reduce histone acetylation by up-regulating expression of histone deacetylases (HDACs) and impair histone methylation, ultimately contributing to down-regulation of brain-derived neurotrophic factor (BDNF) expression and activation of nuclear factor κB (NF-κB) signaling. Neurotoxic effects of Al exposure were also associated with aberrant expression of non-coding RNAs, especially microRNAs (miR). Al-induced patterns of miR expression were involved in development of AD-type pathology by increasing amyloid β (Aβ) production through up-regulation of Aβ precursor protein (APP) and β secretase (BACE1) expression (down-regulation of miR-29a/b, miR-101, miR-124, and Let-7c expression), increasing in neuroinflammation through NF-κB signaling (up-regulation of miR-9, miR-125b, miR-128, and 146a), as well as modulating other signaling pathways. Furthermore, reduced global DNA methylation, altered histone modification, and aberrant miRNA expression were associated with cognitive decline in Al-exposed subjects. However, further studies are required to evaluate the contribution of epigenetic mechanisms to Al-induced neurotoxicity and/or AD development.